Optimalisasi Branding dan Marketing Kerajinan Menjawet Rotan Khas Dayak di Desa Sepang Simin, Gunung Mas, Kalimantan Tengah - Rizkyah; Indahsari, Lilin Ika Nur; Muawwanah, Raudatul; Hafifah, Nur; Sholekhatun, Siti; Nurhaliza, Nurhaliza; Akbar, Reinaldi; Amin , Zulva Sahrul (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Jawet is a traditional weaving technique that has been passed down from generation to generation in the Dayak community of Sepang Simin Village. This handicraft has obstacles, namely the lack of human resources to help and manage the woven jawet products and market them. This community service activity aims to optimize the branding and marketing of the local heritage of jawet weaving craftsmen in Sepang Simin Village, Gunung Mas Regency, Central Kalimantan Province. This community service activity uses the ABCD model for rattan jawet craftsmen. The results of the community service activity show that jawet weaving not only functions as a handicraft product, but also as a symbol of the cultural identity of the local community. Product branding is done by naming the product